KONTRIBUSI PENGALAMAN MENGAJAR, MOTIVASI BERPRESTASI DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU SD DI GUGUS IMAM BONJOL KECAMATAN SAPURAN KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The Contribution of Teaching Experience, Motivation of Having Achievement, and Principal’s Transformational Leadership toward the Elementary School Teachers’ Work at the Imam Bonjol Group of Sapuran Subdistrict of Wonosobo Regency. This research is directed to analyze and prove the contribution of teaching experience, motivation of having achievement, and principal’s transformational leadership simultaneously and independently toward the Elementary School teachers’ work at the Imam Bonjol group of Sapuran subdistrict of Wonosobo regency. This research is carried out at the Imam Bonjol group of Sapuran subdistrict of Wonosobo regency. The population of this research is the Elementary School teachers at the Imam Bonjol group of Sapuran subdistrict of Wonosobo regency. The sampling technique used is Proportional Random Sampling by applying the Slovin’s Formula. Of teachers as much as 108 people obtained a sample of 86 people. In collecting the data, the researcher uses questionnaire. And in analyzing the data, the researcher appliesRegression analysis by using SPSS for window. The research says that there is a significant positive contribution of teaching experience, achievement motivation, and the principal's transformational leadership on teacher performance. It can be concluded that these three variables is a very closely related to the activity of the teaching profession. In the learning activities require teaching experience as a foundation so that teachers have the motivation to excel, while transformational leadership principals motivate teachers also needed to make changes that can improve their performance to obtain maximum results in learning.